Wilson and Gisvold's : textbook of organic medicinal and pharmaceutical chemistry - Doerge, Robert F. (Philadelphia, Pennsylvania : J. B. Lippincott Company, 1982)
This textbook is like the previous seven, it is written for the undergraduate pharmacy student who has previously completed a regular year's course in the fundamentals of organic chemistry.
1.Introduction -- 2. Physicochemical properties in relation to biological action -- 3. Metabolic changes of drugs and related organic compounds -- 4. Anti-infective agents -- 5. Sulfonamides, sulfones and folate reductase inhibitors with antibacterial action -- 6. Antimalarials -- 7. Antibiotics -- 8. Antineoplastic agents -- 9. Central nervous system depressants -- 10. Central nervous system stimulants -- 11. Adrenergic agents -- 12. Cholinergic drugs and related agents.
Includes bibliographical references and index.
Keywords: ORGANIC CHEMISTRY